تأثر التحضر على المرأة الريفية في البيئة البحضرية دراسة ميدانية على نساء من اسر مهاجرة من الريف الى المدينة بالأغواط - نادية بوسوار; لقمان رداف (My University, 2020)
This study aims to identify the impact of urbanization on rural woman in the urban environment, and this is through: Directing the study and shedding light on the rural woman who belongs to a rural family, that woman immigrated to the city, and how this woman tries to adapt the ways of life in the urban environment, which is considered a different new environment from the one where she grew up and whether this effect was positive on her Also we try through this research to study whether the traditional values of the displaced family from the countryside to the city may have a negative impact on the women belonging to it. To achieve the aim of the study, we realized a field study on a sample of rural women who moved to live with their families in the city of Laghouat, whosenumber was estimated at 20 persons, where we collected the information through a questionnaire, and after the collection we analyzed them statistically and sociologically and then concluded with results and we mention here bellow the most important ones: We noticed clearly that women have kept their way of life in the urban environment and the impact of urbanization on them was positive. They admire the city life and the way urban women live and do not feel separated from their new surroundings, Moreover we found that traditional values have a negative effect on rural women in the urban environment and it was not difficult for women to get rid of the Urbanization, Rural women, Urban environment, Traditional values